2019
DOI: 10.1007/s10973-019-08255-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the reaction temperature on the morphology of nanosized HAp

Abstract: We reported on the synthesis of nanosized hydroxyapatite particles by wet chemical precipitation method and the consolidation of the nanoparticles by spark plasma sintering. We studied the effect of the synthesis temperature on the particle size and phase composition of the obtained HAp. During synthesis beyond HAp, another phase supposedly nonstoichiometric HAp was also formed as a by-product that can be detected by thermal analysis combined with XRD. Its amount gradually decreased with the increase in synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…For the material deposited using solution B, an increased crystallinity and crystallite size was determined for the samples deposited at 50 °C compared with those deposited at 37 °C (see Table S1, Supporting Information), which is in accordance with previous studies describing a steady increase in crystallite size with temperature. [ 33 ] FTIR spectra of coatings deposited from both solutions at both temperatures showed peaks corresponding to phosphate and carbonate groups (see Table S2, Supporting Information). Due to the relatively small amount of CaP deposited by solution A, the FTIR spectra of coatings formed with this solution also showed peaks corresponding to contamination by PET from the substrate which was scraped off for analysis along with the coating.…”
Section: Resultsmentioning
confidence: 99%
“…For the material deposited using solution B, an increased crystallinity and crystallite size was determined for the samples deposited at 50 °C compared with those deposited at 37 °C (see Table S1, Supporting Information), which is in accordance with previous studies describing a steady increase in crystallite size with temperature. [ 33 ] FTIR spectra of coatings deposited from both solutions at both temperatures showed peaks corresponding to phosphate and carbonate groups (see Table S2, Supporting Information). Due to the relatively small amount of CaP deposited by solution A, the FTIR spectra of coatings formed with this solution also showed peaks corresponding to contamination by PET from the substrate which was scraped off for analysis along with the coating.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM morphology of CaO (Figure 3B) shows a uniform grain size, HA‐80 (Figure 3C) with a particle size of 39.63 ± 0.73 μm, and HA‐900 (Figure 5D) has an agglomerate shape, solid structure, and uniform particle size of 27.5 ± 0.04 nm. HA‐900 produces nano‐sized crystals with a high synthesis temperature (90°C) with stirring for less than 2 h, and the HA precipitation formed at a short aging time, while the higher synthesis temperature affects a larger crystal size 43 . In this study, HA‐900 with a short aging time resulted in nano‐sized crystals, whereas several studies showed a long aging time (>24 h) produced micro‐sized crystals.…”
Section: Resultsmentioning
confidence: 56%
“…HA-900 produces nano-sized crystals with a high synthesis temperature (90 C) with stirring for less than 2 h, and the HA precipitation formed at a short aging time, while the higher synthesis temperature affects a larger crystal size. 43 In this study, HA-900 with a short aging time resulted in nano-sized crystals, whereas several studies showed a long aging time (>24 h) produced micro-sized crystals.…”
Section: Discussionmentioning
confidence: 55%
“…As seen in Fig. 3f, when CaAlg/HAP was heated at 750 ℃, the HAP particles continued shrinking to the diameter of 20 nm and the nanoparticles were closely arranged on the surface of CaAlg, indicating that the compact surface structure prevented the thermal degradation of CaAlg (György et al 2019).…”
Section: Sem and Xrd Of Caalg And Caalg/hap After Calcination In Airmentioning
confidence: 93%
“…As shown in Table. S1, HAP accounted for 0.974 wt.% in CaAlg/HAP, and HAP was assumed no mass change in TGA for it can exist stably below 1000°C(György et al 2019). If HAP had no effect on the thermal decomposition of CaAlg, the weight loss of CaAlg doped HAP calculated by the theoretical formula should be the same as the experimental CaAlg/HAP.…”
mentioning
confidence: 99%